Advanced concrete technology. - Choo, B. S.; Newman, John (John Brian), 1938- (Butterworth-Heinemann, 2003)
Based on the Institute of Concrete Technology's Advanced Concrete Technology Course, these four volumes are a comprehensive educational and reference resource for the concrete materials technologist. An expert international team of authors from research, academia and industry has been brought together to produce this unique series. Each volume deals with a different aspect of the subject: constituent materials, properties, processes and testing and quality. With worked examples, case studies and illustrations throughout, the books will be a key reference for the concrete specialist for years t.